2020
DOI: 10.1111/ggi.13874
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sit‐to‐stand transfer assistance from a smart walker in older adults with motor impairments

Abstract: Aim To evaluate the effectiveness and user satisfaction with the sit‐to‐stand (STS) assistance system of a smart walker (SW), and to identify factors associated with them in potential users. Methods A total of 33 older adults (29 women, aged ≥65 years) with motor impairments (habitual rollator use) and no severe cognitive impairment (Mini‐Mental State Examination ≥17 points) carried out a Five‐Chair Stand Test without assistance and five STS transfers with the STS assistance system. Based on the number of succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…16% (n = 14) of the studies aimed to support basic daily needs and functions such as nutrition, mobility, medication intake, self‐care, and hearing 56‐69 . The technology used consisted of motion sensors, 63 medication dispensers, 66,67 hearing aids, 56,57 and tablet or mobile apps, 58,65,68 robots, 59,61 a scooter, 60 a smart walker, 62 and electric light wires 64 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…16% (n = 14) of the studies aimed to support basic daily needs and functions such as nutrition, mobility, medication intake, self‐care, and hearing 56‐69 . The technology used consisted of motion sensors, 63 medication dispensers, 66,67 hearing aids, 56,57 and tablet or mobile apps, 58,65,68 robots, 59,61 a scooter, 60 a smart walker, 62 and electric light wires 64 …”
Section: Resultsmentioning
confidence: 99%
“…Three studies were case reports, 57,66,67 one RCT 69 and one qualitative 61 . Results reported were an increase in medication adherence 58,66,67 and improvements or maintenance in activity performance and participation among older participants 59,60,62,65,69 . For the studies focusing on hearing impairment, McInerney and Walden 57 reported positive results with fewer communication breakdowns among the older participants, while in the study by Jupiter, 56 the older participants disliked or simply forgot to use the technology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations